Management of anthracnose (Colletotrichum capsici) in chilli (Capsicum annum L.) through fungicides, bioagents and hand picking methods - R C Gupta, K K Pandey, (Journal of Spices and Aromatic Crops, 2016)
Field trials were conducted on chilli variety LCA-355 for management of anthracnose (Colletotrichum capsici) through fungicides, bioagents and hand picking of initial set of green fruits. The pooled data of two year trials revealed that, minimum percent disease index (PDI) of anthracnose (13.33%) on red chilli fruits was recorded in thrice hand picking of initial set of green chilli fruits. The data also indicated that foliar spray of bioagent Aspergillus niger-V @0.5% with sticker @0.1% resulted in 29.83 PDI which proved to be the second effective treatment. However, highest total yield (1947.95 g plot-1) as well as healthy red chilli fruits (1286.66 g plot-1) was recorded in foliar sprays with Mancozeb @0.3% followed by Azoxystrobin @0.1% (1125.00 g plot-1) and lowest yield in control (550 g plot-1). The highest PDI (59%) of anthracnose on dry red chilli fruits with lowest total yield (1068.97 g plot-1) was recorded in control. The pooled data of field trials revealed that, the thrice hand picking of initial set of green chilli fruits performed better with lowest PDI and proved that hand picking is an effective method for management of anthracnose.